Zoysia japonica Chlorophyll b Reductase Gene NOL Participates in Chlorophyll Degradation and Photosynthesis - Guan, Jin; Teng, Ke; Yue, Yuesen; Guo, Yidi; Liu, Lingyun; Yin, Shuxia; Han, Liebao (Frontiers in Plant Science, 2022)
The degradation of chlorophyll is of great significance to plant growth. The chlorophyll b reductase NOL is in charge of catalyzing the degradation of chlorophyll b and maintaining the stability of the photosystem. However, the molecular mechanisms of NOL-mediated chlorophyll degradation, senescence, and photosynthesis and its functions in other metabolic pathways remain unclear, especially in warm-season turfgrass. In this study, ZjNOL was cloned from Zoysia japonica. It is highly expressed in senescent leaves. Subcellular localization investigation showed ZjNOL is localized in the chloroplast and the bimolecular fluorescence complementation (BiFC) results proved ZjNOL interacts with ZjNYC1 in vivo. ZjNOL promoted the accumulation of ABA and carbohydrates, and the increase of SAG14 at the transcriptional level. ZjNOL simultaneously led to the excessive accumulation of ROS, the activation of antioxidant enzymes, and the generation of oxidative stress, which in turn accelerated senescence. Chlorophyll fluorescence assay (JIP-test) analysis showed that ZjNOL inhibited photosynthetic efficiency mainly through making damage to the oxygen-evolving complex. In total, these results suggest that ZjNOL promotes chlorophyll degradation and senescence and negatively affects the integrity and functionality of the photosystems. It could be a valuable candidate gene for genome editing to cultivate Zoysia japonica germplasm with prolonged green period and improved photosynthesis efficiency.